A design space for automated material handling vehicles - Mirnig, Alexander G.; Fröhlich, Peter; Zafari, Setareh; Gafert, Michael; Kröninger, Lukas; Tscheligi, Manfred (Frontiers in Robotics and AI, 2023)
Material Handling Vehicles (loaders, excavators, forklifts, harvesters etc.) have seen a strong increase of automation efforts in recent years. The contexts such vehicles operate in are frequently complex and due to the often very specific nature of industrial material handling scenarios, knowhow is fragmented and literature not as numerous as, e.g, for passenger vehicle automation.In this paper, we present a contextual design space for automated material handling vehicles (AMHV), that is intended to inform context analysis and design activities across a wide spectrum of material handling use cases. It was developed on the basis of existing context and design spaces for vehicle and machine automation and extended via expert knowledge. The design space consists of separate context and interaction subspaces, that separately capture the situation and each individual point of interaction, respectively. Implications, opportunities and limitations for the investigation and design of AMHV are discussed.